Diagnosis and Treatment Challenges of Candida guilliermondii in Immunocompromised Patients: A Case Study in a Neutropenic AML Patient - Dhruvi Modi; Sophie Dessureault; John Greene (Case Reports in Infectious Diseases)
Although fungal infections causing intestinal perforation and necrosis are rare, they can be particularly dangerous in immunosuppressed patients, often leading to increased mortality rates and poor prognoses. Candida species are typically surface fungi, but in patients with compromised immune systems, they can invade the small intestine and cause angioinvasive infections. A case study involving a 30-year-old female with acute myeloid leukemia (AML) illustrates this phenomenon. The patient was presented with symptoms of abdominal pain, fever, diarrhea, recurrent episodes of intestinal necrosis, hematomas due to thrombocytopenia, and subsequent postoperative enterocutaneous fistulas. Extensive testing ruled out other possible causes of intestinal necrosis and enteritis, including Crohn’s and CMV diseases. Candida guilliermondi was ultimately identified in blood cultures from the periphery, peritoneal fluid, and intestinal biopsy of respected sections, indicating that it was responsible for intestinal invasion and necrosis. The patient was then treated with amphotericin B, cefepime, and metronidazole. This case highlights the potential severity of fungal infections in immunosuppressed patients, particularly Candida species, and the importance of prompt diagnosis and appropriate treatment.